Blood flow and perfusion in acute haemorrhagic pancreatitis in the dog. Issue 8 (August 1986) - Studley, J G; Mathie, R T; Gibbons, M I; Blumgart, L H
Abstract : Experimental evidence suggests that in acute haemorrhagic pancreatitis in the dog the percentage of the cardiac output distributed to the pancreas falls. Histological evidence indicates arteriovenous shunt flow, but this has not been confirmed by flow measurements. It has recently been reported that in experimental preparations in which pancreatic blood flow is measured through the superior pancreaticoduodenal artery after ligation of other (accessory) vessels, perfusion is reduced in distal regions of the gland. There are no data regarding regional perfusion measurements in acute pancreatitis or the effect of ligating accessory vessels. This study therefore evaluates blood flow and regional perfusion in haemorrhagic pancreatitis in various preparations of the canine pancreas. Perfusion was assessed by measuring the clearance of Krypton-85 after injection into the arterial blood supply of the pancreas. Arterial blood flow was measured by the electromagnetic flow technique. The results show that perfusion in different regions of the gland is similar both before and during disease. If accessory vessels are ligated, however, only perfusion in the head of the gland is maintained. No arteriovenous shunt flow was shown. The percentage of the cardiac output being distributed to the gland did not change in any of the experiments; this contradiction to previous reports may arise from the effective control of acid base balance in this study.